From Shamanic Fraud to Serial Murder: Reconstructing Criminal Liability and Causation in an Indonesian Case Study: Dari Penipuan Shamanik hingga Pembunuhan Berantai: Rekonstruksi Tanggung Jawab Pidana dan Kausalitas dalam Studi Kasus Indonesia - Moses Frederick Purba; Mulyadi Mulyadi (Academia Open, 2025)
General Background: Fraudulent shamanic practices exploiting beliefs in supernatural money-doubling persist in Indonesia and have escalated into serious violent crimes. Specific Background: The Banjarnegara serial murder case involving a money-doubling shaman revealed a systematic pattern in which fraud preceded and motivated twelve premeditated killings, adjudicated under District Court Decision No. 63/Pid.B/2023/PN Bnr. Knowledge Gap: Prior studies rarely examine the integrated construction of criminal liability combining fraud, premeditated murder, participation, and concursus realis, particularly in comparison with the preventive framework of the new Criminal Code. Aims: This study analyzes the layered application of criminal provisions under the old Criminal Code and compares them with the new Criminal Code to assess proportional accountability and sanctions. Results: The findings show that fraud under Article 378 functioned as the proxima causa triggering premeditated murder under Article 340, aggravated by participation (Article 55) and multiple offenses (Article 65), justifying the imposition of the death penalty despite the introduction of Article 252 of Law No. 1 of 2023. Novelty: The study conceptualizes fraud as a causal foundation for serial premeditated murder within a concursus realis framework. Implications: These findings reinforce the need for integrated repressive and preventive criminal policies to address extraordinary crimes rooted in deceptive supernatural claims. Highlights: Fraud functions as the causal trigger for systematic premeditated murder. Layered application of criminal provisions strengthens proportional accountability. Preventive norms in the new Criminal Code remain insufficient for extraordinary crimes. Keywords: Criminal Liability, Premeditated Murder, Fraudulent Shamanism, Concursus Realis, Death Penalty